Policy Implications on Carbon Labeling Scheme Toward Carbon Neutrality in China - Zhao, Rui; Wu, Dingye; Zhang, Junke (Frontiers in Environmental Science, 2021)
Carbon labeling scheme as a quantitative measure on carbon emissions of product or service, can be applied to lead low carbon consumption and production, which is also a powerful tool to achieve carbon neutral. The policy brief reviews the progress of carbon labelling scheme to provide insight into its future perspectives on carbon neutrality in China. The results show that: ① China has not fostered as a carbon labeling system, but there is pilot attempt to electric appliance; ② Publics’ perception towards carbon labeling scheme is in a lower level, since China has not officially fostered such a labelling system; ③ There is a room for improvement on existing carbon labeling scheme, to highlight its transparency and comparison.